IMPLEMENTASI APLIKASI SAKTI TERHADAP AKURASI DATA PERSEDIAAN BARANG OPERASIONAL PADA KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN UTAMA BELAWAN - Handika Salim Siagian; Ratna Dina Marviana; Listya Devi Junaidi; Lukman Hakim Siregar (Worksheet : Jurnal Akuntansi, 2026)
This study aims to analyze the implementation of the Institutional Financial Application System (SAKTI) on the accuracy of operational inventory data at the Belawan Main Port Authority Office. This study uses a descriptive method with a qualitative approach, with data collection techniques through interviews, observations, and documentation of employees involved in inventory management and the operation of the SAKTI Application. The results show that the implementation of the SAKTI Application can improve the efficiency and integration of the system in the inventory recording and reporting process through the integration of financial modules, as well as the existence of a system validation feature that helps minimize recording errors, thereby improving the accuracy of inventory data. However, there are still several obstacles in its implementation, such as dependence on the internet network and the use of manual recording as an operational tool, which causes delays in data input into the system. Overall, the implementation of the SAKTI Application has made a positive contribution to improving inventory data accuracy and supporting transparency and accountability in the management of operational goods at the Belawan Main KSOP.Keyword:SAKTI implementation, data accuracy, operational inventory.